LAMINAR AIDING COMBINED CONVECTION IN THE DEVELOPING REGION OF INCLINED CYLINDER (Journal of Engineering, 2011)
The influence of natural convection due to buoyancy on the laminar upwards air flow in a uniformly heated inclined circular cylinder has been experimentally studied. The investigation covered a wide range of Reynolds number (450≤Re≤2008), heat flux (95 ≤ q ≤ 898) W/m2, Rayligh number (1.1132×105 ≤ Ra ≤ 3.6982×105 ), with different angles of cylinder inclination α=0° (Horizontal), α=30°, α=60° (Inclined) and α=90° (Vertical).Results show that the heat transfer process improves as the angle of inclination moves from vertical to horizontal position. A general empirical equation for average Nusselt number Num as a function of Rayligh number Ra, Reynolds number Re and angle of inclination α was obtained.